Application of the guided note-taking method assisted by the Moovly application in learning to evaluate information in fable texts for class X students at SMK Nasional Bandung - Dimas Aji Santoso; Dheni Harmaen; Aries Setya Nugraha (Journal of Practice Learning and Educational Development, 2026)
Learning plays an important role in improving students’ literacy skills, especially in evaluating information in hikayat texts. However, classroom conditions show that students’ evaluation skills remain low due to monotonous teaching methods that reduce students’ activeness and understanding. This study aims to analyze the researcher’s ability to design and implement learning activities and to examine the effectiveness of the guided note-taking method assisted by the Moovly application for Grade X students of SMK Nasional Bandung. This research employed a quantitative experimental design involving an experimental class and a control class. The lesson planning score reached 95 and the learning implementation score reached 98, both categorized as very good. Students’ pretest results were in the developing category. After the treatment, the experimental class achieved an average posttest score of 65. The N-Gain score of the experimental class was 59.47 (moderately effective), while the control class obtained only 33.10 (ineffective). The Mann–Whitney test produced a significance value of 0.036, indicating a significant difference between the two classes. Therefore, the guided note-taking method supported by the Moovly application is moderately effective in improving students’ ability to evaluate information in hikayat texts.